Discovery and Characterization of the Naturally Occurring Inhibitors Against Human Pancreatic Lipase in Ampelopsis grossedentata - Qin, Xiao-Ya; Hou, Xu-Dong; Zhu, Guang-Hao; Xiong, Yuan; Song, Yun-Qing; Zhu, Liang; Zhao, Dong-Fang; Jia, Shou-Ning; Hou, Jie; Tang, Hui; Ge, Guang-Bo (Frontiers in Nutrition, 2022)
Pancreatic lipase inhibitor therapy has been validated as an efficacious way for preventing and treating obesity and overweight. In the past few decades, porcine pancreatic lipase (pPL) is widely used as the enzyme source for screening PL inhibitors, which generates a wide range of pPL inhibitors. By contrast, the efficacious inhibitors against human pancreatic lipase (hPL) are rarely reported. This study aims to discover the naturally occurring hPL inhibitors from edible herbal medicines (HMs) and to characterize the inhibitory mechanisms of the newly identified hPL inhibitors. Following screening of the inhibition potentials of more than 100 HMs against hPL, Ampelopsis grossedentata extract (AGE) displayed the most potent hPL inhibition activity. After then, the major constituents in AGE were identified and purified, while their anti-hPL effects were assayed in vitro. The results clearly showed that two abundant constituents in AGE (dihydromyricetin and iso-dihydromyricetin) were moderate hPL inhibitors, while myricetin, and quercetin were strong hPL inhibitors (IC50 values were around 1.5 µM). Inhibition kinetic analyses demonstrated that myricetin, and quercetin potently inhibited hPL-catalyzed DDAO-ol hydrolysis in a non-competitive inhibition manner, with Ki values of 2.04 µM, and 2.33 µM, respectively. Molecular dynamics simulations indicated that myricetin, and quercetin could stably bind on an allosteric site of hPL. Collectively, this study reveals the key anti-obesity constituents in AGE and elucidates their inhibitory mechanisms against hPL, which offers convincing evidence to support the anti-obesity and the lipid-lowering effects of this edible herb.